A method for improving temperature measurement precision on the uncooled infrared thermal imager. (October 2015) - Zhang, Yu-cun; Chen, Yi-ming; Luo, Cheng
Highlights: Infrared temperature measurement precision is improved by eliminating interior radiation. Thermal imager temperature measurement model is established based on voltage compensation. The relationship between image pixels value and temperature of the object is obtained. The absolute temperature on the surface of tested object can be measured accurately. Abstract: In order to improve temperature measurement precision of the uncooled infrared thermal imager, aiming at the influence of the thermal imager internal radiation, a method is proposed based on voltage compensation in this paper. Firstly, combining the principle of uncooled infrared thermal imager, radiation of tested object is converted to voltage values, the voltage values are converted to grey value can be measured, and thus the relationship between radiation of tested object and grey value is established. Secondly, according to the relationship between radiation and grey value, a model about uncooled infrared thermal imager temperature measurement is established. A formula for computing the true surface temperature of objects is given. Coefficients are acquired in the temperature measurement formula by collecting the infrared image data of standard blackbody. Finally, in order to verify the correctness of the compensation method, an experiment about blackbody is conducted in this paper. The experiment results show that this method can effectively reduce the relative error of the thermal imager temperature measurement.